Factors influencing attendance to eye screening among diabetes mellitus patients in Kuantan, Pahang - Rif'atunnailah binti Mat Isa (2018)
Diabetes Mellitus (DM) is on a rising trend globally and the complications of DM particularly diabetic retinopathy are kept on escalating. However, the number of patients who underwent proper eye screening in Malaysia is still far from satisfactory. The aim of this thesis is to identify the facilitating factors, barriers for DM patients to go for eye screening, and to explore the current management of eye screening for diabetic patients and how it influences the attendance for routine eye screening. This study used a mixed-method study design. The quantitative involves a cross-sectional survey of 170 participants using self-administered questionnaires. The data was analysed descriptively using SPSS in understanding the facilitators and barriers for eye screening among diabetes patients. Subsequently, ten in-depth face to face semi-structured interviews with healthcare professionals with additional of document analysis was conducted to understand the eye screening provision in the study settings. The qualitative data was managed manually and analysed thematically. Majority of participants 45.9 % (n=78) highlighted that lack of information regarding diabetes and not understanding the significance of eye screening are the barriers to eye screening. Whereas 10.6% (n=18) reported lack of access to healthcare facilities, 6.5% (n=11) experienced time limitation and 2.9% (n=5) suffered financial issues. However, more than half of participants (58.2%) have good knowledge related to diabetic eye complication. There is a significant difference between educational level with patients' attendance in yearly eye screening; χ2 = 8.32, df = 2, p<0.05. From qualitative part, the factors that influence the attendance to eye screening were; health care providers' confidence in performing eye screening, effectiveness of green card system, interactive health educational session and continuous support from family members. Lack of information received by the patients on the importance of eye screening and communication issues seems to be prominent and become the reasons for patients' not attending eye screening. Having a structured programme which emphasises on the importance of eye screening could be able to empower the patients and facilitate better communication strategy between patients and healthcare professionals. This simultaneously would increase the interest of the patient to follow the schedule of eye screening in order to achieve better health outcomes. For further research, the improvement of default tracking systems and the provision of eye-related educational material are important to enhance health literacy among diabetic patients and the population of Malaysia.